La captation et ses paradoxes. Réflexions sur la mise en vidéo des concerts à l’ère de la plateformisation de la musique - Michaël Spanu; Catherine Rudent (Communiquer)
The massive circulation of concert videos on digital platforms questions more than ever the concert as an exclusive ritual. In France, these videos are called “captation” (video recording). This article aims at discussing the multiple paradoxes of this term. For this purpose, we rely on an exploratory investigation conducted with French professionals in 2019. In the first section of the article, we highlight the inherent tension between secret and publicity to the concert situation that still operates in a digital era. In the second section, we investigate the paradoxical attempt to transpose the exclusive dimension of a concert on a screen, in the shape of a document. In the last section, we argue how concert videos can go beyond the document paradigm under certain conditions, becoming performative objects that affect the concert in return, especially in the context of digital platforms. Each paradigm entails specific questions related to aesthetics, economy and heritage.